Revision of the Afrotropical endemic Eumerus triangularis group (Diptera: Syrphidae: Merodontini) – Species with glistering antennae - Snežana Radenković; Nevena Veličković; Kurt Jordaens; Ana S. Grković; Mihajla Djan; Gunilla Ståhls; John Smit; Ante Vujić (PLoS ONE, 2025)
The Eumerus triangularis group (Diptera: Syrphidae: Merodontini), which is endemic to the Afrotropical Region, has been thoroughly reviewed. This study identifies nine species within the group, with four of them redescribed: E. rubidus Hull, 1964, E. tessellatus Hull, 1964, E. triangularis Hervé-Bazin, 1913, and E. villeneuvei Hervé-Bazin, 1913 and with the description of four new species – E. argentipedicellus Radenković, Vujić & Grković sp. nov., E. brunnipennis Radenković, Vujić & Grković sp. nov., E. clavicercus Radenković, Vujić & Grković sp. nov., and E. setifemoratus Radenković, Vujić & Grković sp. nov. Furthermore, the previously unknown male of E. rubidus and the female of E. tessellatus are described. This study includes illustrated identification keys for males and females, along with detailed drawings of male terminalia for all nine species. DNA sequences of two regions of the mitochondrial DNA, cytochrome c oxidase subunit 1 (COI) gene and cytochrome b, and a region of the nuclear ribosomal 28rRNA gene are used to confirm morphological identification. Both molecular and morphological analyses indicate the presence of two distinct clades within the E. triangularis species group.